An Alternative Method of Reporting Research: Evaluation by Editors and Reporters - Gerald W. McGee (Journal of Applied Communications, 1979)
"Research Review " is a tip sheet carrying short descriptions of previously unreported and ongoing research projects in the College of Agriculture and life Sciences at the University of Wisconsin-Madison.